Policing Muslim Communities - Hakeem, Farrukh B. author. aut Link
IX, 146 p. 12 illus.
Keywords: Recently the Islamic world is undergoing political crisis and social unrest, in no small measure due to conflict between traditionalism and modernism. At the center of this contention is the role of Sharia in Muslim society and the keeping of order. With this global discourse in mind, Policing Muslim Communities: Comparative International Context examines Sharia and its compatability with modern law enforcement. Issues and challenges regarding policing in Sharia-based, secular, and blended Islamic communities, communities under authoritarian and military control, and Muslim communities in non-Muslim countries are discussed in the current contexts of the human rights movements and global technologies. Balancing the perspectives of policing, by Muslims, with Muslims, and of Muslims, the book: Offers a concise summary of the normative foundations of Sharia and its implications for policing and law enforcement. Discusses in depth policing practices in Muslim-majority and mixed systems. Contrasts various approaches to policing, case processing, and training in today’s socio-political context. Traces the effects of historical events such as the socio-political change in Muslim societies on modern law enforcement. Provides insights into the preventive/proactive role of the community as a basis for an international model of policing. Features case studies from across the Muslim world. Timely reading that fills a major knowledge void, Policing Muslim Communities: Comparative International Context will find a wide audience among criminologists, political scientists, religious scholars, scholars of Islam, and public policymakers.